2021
DOI: 10.1002/ajh.26063
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sickle cell disease on patientsʼ daily lives, symptoms reported, and disease management strategies: Results from the international Sickle Cell World Assessment Survey (SWAY)

Abstract: Sickle cell disease (SCD) is a genetic disorder, characterized by hemolytic anemia and vaso‐occlusive crises (VOCs). Data on the global SCD impact on quality of life (QoL) from the patient viewpoint are limited. The international Sickle Cell World Assessment Survey (SWAY) aimed to provide insights into patient‐reported impact of SCD on QoL. This cross‐sectional survey of SCD patients enrolled by healthcare professionals and advocacy groups assessed disease impact on daily life, education and work, symptoms, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 40 publications
2
74
0
Order By: Relevance
“…Nevertheless, a single center study investigating parental stress in relationship to chronic hematological disorders, included also parents of children with SCD and reported higher stress among parents of children with SCD compared to those of children with Immune Trombocytopenic Purpura [23]. Italian patients and caregivers participated also in the International Sickle Cell World Assessment Survey (SWAY) in which emotional and wellbeing were accessed globally through a dedicated survey: significant impact of SCD on clinical, emotional, psychological and social aspects of life were reported [24].…”
Section: Existing Literature On Qol and Scd In Italymentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a single center study investigating parental stress in relationship to chronic hematological disorders, included also parents of children with SCD and reported higher stress among parents of children with SCD compared to those of children with Immune Trombocytopenic Purpura [23]. Italian patients and caregivers participated also in the International Sickle Cell World Assessment Survey (SWAY) in which emotional and wellbeing were accessed globally through a dedicated survey: significant impact of SCD on clinical, emotional, psychological and social aspects of life were reported [24].…”
Section: Existing Literature On Qol and Scd In Italymentioning
confidence: 99%
“…Moreover, Italian teenagers and adults with SCD as well as guardians were among the global population of patients completing the International Sickle Cell World Assessment Survey (SWAY) [24] in which the improvement of QoL was ranked as the first top treatment goal in the 6-11, 12-16 and 17-18 year old age groups. Adolescents with SCD living in Italy have also demonstrated a high completion rate of the daily electronic patient-reported outcome (PRO) diary in the international DOVE trial [29] further underscoring their interest in being involved to report PROs.…”
Section: Commentmentioning
confidence: 99%
“…13 In a robust international sample, more than a third of individuals with SCD reported that the disease impacted their participation in daily household chores and social activities. 14 Medication adherence, another aspect of IADL skills, is often poor among youth and adults with SCD. 15 Workforce and educational engagement represent another marker of IADL skills.…”
Section: Introductionmentioning
confidence: 99%
“…Acute painful vaso‐occlusive crisis (VOC) is one of the clinical hallmarks of sickle cell disease (SCD) 1 . VOCs account for the vast majority of SCD‐related hospital admissions and are associated with significant morbidity and mortality, and negatively impact quality of life 2–5 . Despite the improvements made in our understanding of the pathophysiology of VOC, its treatment still primarily consists of supportive care 6 .…”
Section: Introductionmentioning
confidence: 99%
“…1 VOCs account for the vast majority of SCD-related hospital admissions and are associated with significant morbidity and mortality, and negatively impact quality of life. [2][3][4][5] Despite the improvements made in our understanding of the pathophysiology of VOC, its treatment still primarily consists of supportive care. 6 Besides treatment of a potential underlying cause, extra [intravenous (IV)] fluids, (opioid) analgesics, and occasionally oxygen support are part of the treatment of VOC.…”
Section: Introductionmentioning
confidence: 99%